(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Microelements play a fundamental role in maintaining the electrophysiological stability of the pediatric myocardium. Deficiencies of key trace elements - particularly magnesium, potassium, calcium, zinc, selenium, and iron - can disrupt ion channel function, myocardial excitability, and cardiac conduction pathways. Children, due to rapid growth and higher metabolic demand, are especially vulnerable to such deficiencies. This article reviews current evidence regarding the contribution of microelement imbalance to the development of arrhythmias in children, highlights pathophysiological mechanisms, and discusses diagnostic and preventive considerations.